Diagnosis of sirenomelia in the first trimester. Issue 6 (27th November 2013) - Singh, Chanchal; Lodha, Pooja; Arora, Deepshikha; Prabhu Sharma, Akshatha; Kaul, Anita
ABSTRACT Sirenomelia or "mermaid syndrome" is a rare congenital abnormality with an incidence of 1 in 60, 000. We report a case diagnosed in the first trimester using two‐dimensional, three‐dimensional, and color Doppler ultrasound. With increasing emphasis on early diagnosis of fetal abnormalities, this case highlights the importance of looking for anomalies in the first trimester itself. In fact, the diagnosis of sirenomelia should be easier in the first trimester as severe oligohydramnios in later gestation hampers vision. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound42:355–359, 2014